Co-encapsulation of bacterial spores and nutrients by polyethylene glycol for self-sealing cementitious composites - Feng, Jianhang (2024)
Co-encapsulation of endospores and nutrients in self-healing concrete can mitigate their negative effects on cement hydration. However, the current approaches of co-encapsulation for bacteria-based self-healing cementitious composites could cause pre-consumption of nutrients before cracking or a restricted release of nutrients after cracking. To address the nutrient release issue, polyethylene glycol (PEG) with high solubility was applied as an alternative to co-encapsulation of bacterial spores and nutrients, subsequently coated by an epoxy/sand protective shell herein. The core-shell structured capsules rapidly released the encapsulated substances within approximately 4 h and protected the encapsulated endospores in alkali environments. Due to the co-encapsulation, hydration retardation was avoided, leading to less severe reductions in compressive strength. After cracking, although the released amount of nutrients decreased after encapsulation, the closure of cracks below 300 μm was improved in the presence of capsules, thus water tightness was recovered more significantly. A model was developed to simulate sealing evolutions, and the modelling results were generally consistent with the experimental results.